Respect, freedom, citizenship: Muslim women's secularities and perspectives on wellbeing. Issue 1 (1st January 2022) - Pool, Fernande W.
ABSTRACT: The religiosity of people migrating into secular European countries has posed many questions for policymakers and scholars alike, particularly where it concerns Islam. Rather than opposing migrants' religious identities with secular values, this article examines shifts and tensions between the 'multiple secularities' of Muslim women and integration policy alike, through an ethnography of wellbeing. Set in the Netherlands, it demonstrates that Muslim women of Pakistani background embrace a secularity characterised by respect and religious liberty but that despite a 'modernisation' of values, their religion remains the source of their secularity. Dutch integration policy, however, has shifted from a secularity accommodating religious diversity to one characterised by individual liberty (placed in opposition to religion), and, increasingly, towards the progress of a culturally homogeneous nation. By thus failing to recognise religious sources and alternative social dimensions of human wellbeing, Dutch policy risks undermining secular values generally and alienating Dutch Muslims specifically.